2001
DOI: 10.1182/blood.v97.9.2758
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-11 induces Th2 polarization of human CD4+ T cells

Abstract: IntroductionInterleukin (IL)-11 is a multifunctional cytokine that was originally isolated from the primate stromal cell line, PU-34, and later from the human MRC 5 cell line. Biologic characterization has shown diverse effects on a variety of hematopoietic and nonhematopoietic cell types (reviewed in reference 1). Due to its ability to stimulate megakaryopoiesis and thrombopoiesis, IL-11 has been approved in the United States for the treatment of chemotherapy-induced thrombocytopenia. In addition to stimulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
72
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 80 publications
(72 citation statements)
references
References 21 publications
0
72
0
Order By: Relevance
“…Murine L cells stably transfected with the human CD40L (CD154) cDNA 49,50 were cultured in RPMI 1640 (Cambrex Bio Science, Verviers, Belgium) supplemented with penicillin/streptomycin, L-glutamine, and 10% heat-inactivated FCS (Cambrex Bio Science). Isolated CLL B cells were cocultured with CD40L-transfected cells in 24-well plates for 72 hours.…”
Section: Cells and Culture Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Murine L cells stably transfected with the human CD40L (CD154) cDNA 49,50 were cultured in RPMI 1640 (Cambrex Bio Science, Verviers, Belgium) supplemented with penicillin/streptomycin, L-glutamine, and 10% heat-inactivated FCS (Cambrex Bio Science). Isolated CLL B cells were cocultured with CD40L-transfected cells in 24-well plates for 72 hours.…”
Section: Cells and Culture Conditionsmentioning
confidence: 99%
“…39 PBMCs were isolated by density gradient centrifugation (Ficoll; Biochrom, Berlin, Germany) and subjected to a preliminary phenotypic characterization. When residual non-B cells exceeded 10%, B cells were enriched by negative selection with antibody-coated magnetic beads (CD2-beads; Dynal, Oslo, Norway) to obtain a more than 95% pure CD19 ϩ /CD5 ϩ B-cell population.Murine L cells stably transfected with the human CD40L (CD154) cDNA 49,50 were cultured in RPMI 1640 (Cambrex Bio Science, Verviers, Belgium) supplemented with penicillin/streptomycin, L-glutamine, and 10% heat-inactivated FCS (Cambrex Bio Science). Isolated CLL B cells were cocultured with CD40L-transfected cells in 24-well plates for 72 hours.…”
mentioning
confidence: 99%
“…Similar to IL-6, IL-11 induces STAT3 phosphorylation in several noninflammatory cell subsets (26)(27)(28)(29) and induces autoreactive Ab production by B cells (30). Several studies have reported on the IL-11 anti-inflammatory effects, including the inhibition of NF-kBmediated cytokine secretion in macrophages (31,32) and monocytes (22), and the induction of apoptosis in myeloid dendritic cells (23,33). However, in the recent literature, IL-11 has been strongly implicated as a proinflammatory cytokine because of its induction by oxidative stress (34), its production by synoviocytes in rheumatoid arthritis (35), and by eosinophils in atopic dermatitis (36).…”
mentioning
confidence: 99%
“…Furthermore, we have identified IL-11 as a new Th17-promoting cytokine. IL-11 is a pleiotropic cytokine (21)(22)(23) and a member of the IL-6 family, with which it shares a gp130 signaling pathway (24). IL-11 competes with IL-6 for binding to the same gp130 epitopes and induces the same early response genes (25).…”
mentioning
confidence: 99%
“…Such modulation was potentially promoted by the simultaneous decrease in levels of TNF␣ and IL-7, both key antagonists of Treg cell-induced immunoregulation (46). Down-regulation of CD40, IL-10, and IL-11 (47) may further suggest that Th2-associated responses were modulated by treatment. An effect of Hsp60 on B cells through innate signaling pathways has been reported (48) and may also contribute to the modulation of autoimmune diseases with a confirmed or potential B cell aspect.…”
Section: Discussionmentioning
confidence: 99%